NanoporeInspect: An interactive tool for evaluating nanopore sequencing quality and ligation efficiency - Grigoryeva, Maria A; Khrenova, Maria G; Zvereva, Maria I (Journal of bioinformatics and computational biology, 2025)
In nanopore sequencing, especially in SELEX-based aptamer discovery, the correct ligation of artificial sequences (primers, adapters, barcodes) is crucial for library quality. Errors at this stage can lead to misidentification of sequences and loss of valuable information. Existing quality control tools lack focused capabilities to assess the positioning and prevalence of these artificial sequences. NanoporeInspect is a web-based tool designed to fill this gap by providing targeted insights into ligation efficacy and systematic biases within sequencing data. NanoporeInspect operates as a user-friendly, web-based platform that leverages a modern software stack with Flask, Celery and Redis to handle scalable and asynchronous task processing, and Plotly to deliver interactive visualizations. Evaluation of NanoporeInspect on various nanopore datasets demonstrated its effectiveness in discerning differences in ligation quality. Libraries with inefficient ligation showed irregular adapter and barcode distributions, indicating preparation issues, while high-quality libraries displayed uniform patterns, reflecting effective ligation.